Amperometric biosensor for direct blood lactate detection - Romero, Marcelo Ricardo (2010)
An amperometric sensor for lactate quantification is presented. The developed biosensor requires only 0.2 U of lactate oxidase, which is immobilized in a mucin/albumin hydrogel matrix. By protecting the platinum surface with a Nafion membrane, typical interference related to negatively charged species such as ascorbic acid has been minimized to practically undetectable levels. Electrochemical properties associated with the Nafion membrane are assessed as a function of Nafion concentration. In a phosphate buffer solution of pH 7.0, linear dependence of the catalytic current upon lactate bulk concentration was obtained between 2 and ∼1000 μM. A detection limit of 0.8 μM can be calculated considering 3 times the standard deviation of the blank signal divided by the sensitivity of the sensor. The lactate biosensor presents remarkable operational stability and sensitivity (0.537 ± 0.007) mA.M-1, where the error is the standard deviation of the slope calculated from the linear regression of the calibration curve of a fresh biosensor. In this regard, the sensor keeps practically the same sensitivity for 5 months, while the linear range decreases until an upper value of 0.8 mM is reached. Assays performed with whole blood samples spiked with 100 μM lactate gave (89 ± 6)% of recovery. © 2010 American Chemical Society.